2019
DOI: 10.2217/cer-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adherence of biologics in US patients with psoriatic arthritis: analyses from a claims database

Abstract: Aim: To evaluate the persistence and adherence of subcutaneous biologics in patients with psoriatic arthritis (PsA). Patients & methods: Psoriatic arthritis patients who initiated adalimumab, certolizumab pegol, etanercept, golimumab or secukinumab between 15 January 2016 and 31 July 2017 were identified in the Truven Databases. Outcomes included discontinuation rate, persistence and adherence over 12 months. Results: Of 1558 patients included, the 12-month discontinuation rate was lowest with secukinumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 42 publications
10
37
1
1
Order By: Relevance
“…Our results suggest that patients who remained on a biologic experienced a decreased economic burden, because those who switched or discontinued biologics had higher medical costs and increased healthcare resource utilization, while patients who switched also had higher pharmacy costs. Overall, 54.8% of patients remained on the index biologic, 18.5% switched the biologic, and 26.7% discontinued the biologic therapy within the 1-year follow-up period; these results are similar to those from previous studies using the Humana US claims database to evaluate switching patterns across multiple immune-mediated diseases, including rheumatoid arthritis, ankylosing spondylitis, psoriasis, and PsA [30], and in the Truven databases among patients with PsA [32]. From the Humana US claims database, Howe and colleagues reported that both new patients and continuing patients had similar mean annual costs per treated patient; however, continuing patients had the highest medical costs, whereas new patients had the highest pharmacy costs [30].…”
Section: Discussionsupporting
confidence: 83%
“…Our results suggest that patients who remained on a biologic experienced a decreased economic burden, because those who switched or discontinued biologics had higher medical costs and increased healthcare resource utilization, while patients who switched also had higher pharmacy costs. Overall, 54.8% of patients remained on the index biologic, 18.5% switched the biologic, and 26.7% discontinued the biologic therapy within the 1-year follow-up period; these results are similar to those from previous studies using the Humana US claims database to evaluate switching patterns across multiple immune-mediated diseases, including rheumatoid arthritis, ankylosing spondylitis, psoriasis, and PsA [30], and in the Truven databases among patients with PsA [32]. From the Humana US claims database, Howe and colleagues reported that both new patients and continuing patients had similar mean annual costs per treated patient; however, continuing patients had the highest medical costs, whereas new patients had the highest pharmacy costs [30].…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in line with guidelines from the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) and American College of Rheumatology, which recommend that patients who experience a lack of response or tolerability issues with biologic therapy should switch to another biologic or to a treatment with a different mechanism of action [ 29 , 37 , 38 ]. Mean adherence rates among patients in the apremilast and biologic cohorts in our study (PDC 0.84 and 0.82, respectively) were higher than mean adherence rates in a recent claims-based analysis of patients with PsA receiving treatment with biologic agents (PDC ranging from 0.49 to 0.67) [ 39 ]. These differences may be due to variations in treatment history or other patient characteristics between the study populations.…”
Section: Discussioncontrasting
confidence: 71%
“…In large observational studies comparing adherence, retention and persistence rates with various bDMARDs in patients with PsA, results were mixed. In a retrospective cohort study using US pharmacy claims data (n = 1558), the 12-month discontinuation rate was lowest with secukinumab (37%), followed by adalimumab (43%), golimumab (45%), etanercept (48%) and certolizumab pegol (52%) [45]. Mean persistence ranged from 241 days with certolizumab pegol to 283 days with secukinumab.…”
Section: Real-world Settingmentioning
confidence: 99%